Effect of commerically prepared wax coating on the ripening period of freshly harvested mangoes (Mangifer indica L. c.v. carabao) - Binguan, Sherwin E.
Freshly harvested carabao mangoes were treated with a commercially prepared ready-to-use wax coating (Sta Fresh 320) presently used in citrus fruits, to increase the fruits ripening period.